Diagnostic pediatric ultrasound - Beek, Erik; Rijn, Rick R. van (Thieme, 2016)
""Diagnostic Pediatric Ultrasound is a complete "go-to" reference for daily practice. It clearly shows why ultrasound is the pediatric imaging modality of first choice, offering safe, noninvasive, high-quality results, leading to an accurate diagnosis. It provides a wide range of normal reference images for comparison with pathologic findings. This book contains instructive ultrasound videos available on Thieme Media Center showing diagnoses.""--Provided by publisher.